PENGEMBANGAN POTENSI DIRI DALAM PEMBELAJARAN SELAMA PANDEMI COVID 19 (STUDI KEPUSTAKAAN BUKU “MALAS TAPI SUKSES” KARYA FRED GRATZON) - Muhammad Fauzy Emqi; Riantina Fitra Aldya (Universitas Tribhuwana Tunggadewi, 2021)
This study aims to determined self-potential in learning during the COVID-19 pandemic, through a literature study of a work entitled